2022
DOI: 10.3390/toxics10080436
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ferroptosis in the Damage of Human Proximal Tubule Epithelial Cells Caused by Perfluorooctane Sulfonate

Abstract: Perfluorooctane sulfonate (PFOS) is a typical persistent organic pollutant and environmental endocrine disruptor that has been shown to be associated with the development of many diseases; it poses a considerable threat to the ecological environment and to human health. PFOS is known to cause damage to renal cells; however, studies of PFOS-induced ferroptosis in cells have not been reported. We used the CCK-8 method to detect cell viability, flow cytometry and immunofluorescence methods to detect ROS levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Liver: hepatotoxic NAFLD, liver fibrosis, markers change [198,200,385,[386][387][388] 2. Kidney: nephrotoxic Reduced excretion of toxins [204,389,390]; increased incidence of CKD [203,391]; ferroptosis [392] 3. Lungs/bronchi Promotion of asthma in youth [393] 4.…”
Section: Affected Organ/function Consequencesmentioning
confidence: 99%
“…Liver: hepatotoxic NAFLD, liver fibrosis, markers change [198,200,385,[386][387][388] 2. Kidney: nephrotoxic Reduced excretion of toxins [204,389,390]; increased incidence of CKD [203,391]; ferroptosis [392] 3. Lungs/bronchi Promotion of asthma in youth [393] 4.…”
Section: Affected Organ/function Consequencesmentioning
confidence: 99%
“…The study further suggested the involvement of ferroptosis in PFAS-induced effects, indicating the potential role of this mechanism in the toxicological response to PFCs. Moreover, the role of ferroptosis was also examined in PFOS-induced endothelial dysfunction . PFOS exposure was found to cause a decrease in cell viability and morphological changes and increased lipid droplet accumulation in human umbilical vein endothelial cells (HUVECs).…”
Section: Ferroptosis Inducers In Environmental Pollutantsmentioning
confidence: 99%
“…Moreover, the role of ferroptosis was also examined in PFOS-induced endothelial dysfunction. 78 PFOS exposure was found to cause a decrease in cell viability and morphological changes and increased lipid droplet accumulation in human umbilical vein endothelial cells (HUVECs). Furthermore, PFOS downregulated the expression of GPX4 and ferritin heavy chain protein 1 (FTH1) while upregulating ACSL4.…”
Section: Perfluorochemicals (Pfcs)mentioning
confidence: 99%